INTEGRASI PENDIDIKAN AGAMA DAN SAINS DI MADRASAH - Moh Farhan; Hidayatus Solihah; Samsudin Samsudin (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2021)
This article explains the integration between religious education and science that occurs in Madrasah Aliyah Negeri 2 MAN, Kudus, based onboarding school Darul Adzkiya. The jargon "raising intellectually religious students", adds to the spirit of integration for religious education and science. MAN 2 Kudus was chosen because the school became one of the leading Madrasah (Islamic School. Methods This research used a qualitative approach. In collecting data, various methods were used such as observation, literature review, and interviews. The results of this study are the integration of religious education and science carried out at the Darul Adzkiya MAN 2 Kudus Boarding School through the formation of religious and science curriculum in the Darul Adzkiya MAN 2 Kudus Boarding School curriculum structure, designing the Bilingual Class System - Science (BCS Science) Program and also improving infrastructure.Keywords: Integration, Religion and Science, Boarding School